Shrimp culture packages in southwestern Bangladesh - Sarkar, D; Sayeed, MAB; Hossain, GS; Huq, KA (Journal of Bio-Science, 2012)
Context: The study was conducted under the technical support of ATDP-II in Bagerhat District, from July to November 2005 on traditional, closed, and semi-intensive culture packages of penaeid shrimp (Penaeus monodon). Objective: The objective of the study was to compare the management, technical and economic aspects of three different shrimp culture packages. Materials and Methods: Post larval nursing was done for 30 days at a density of 50 PL/m2. Culture was done for 120 days at a density of 2.11, 7.37 & 11.56 individuals/m2 in traditional, closed, and semi-intensive ponds respectively. Shrimp PL were fed CP feed (40 % protein) at a rate of 2kg for 100,000 PL, but no supplementary feed was used in traditional ponds. Results: The highest average daily growth (0.263±0.026 g/day) was found in traditional culture; while in closed, and semi-intensive system it was lower (0.226±0.023 and 0.239±0.022 g/day respectively) due to high stocking density and feed competition. Survival rates were found 49.14±5.94, 57.94±8.01 and 60.07±10.98 % which yielded 327.23±24.14, 1158.07±134.76, 1991.57±232.70 kg/ha in traditional, closed, and semi-intensive ponds respectively. Net income was calculated 47932.18 Tk/ha from traditional, 178779.2 Tk/ha from closed, and 312736.8 Tk/ha from semi-intensive culture. Conclusion: The study suggests that instead of horizontal expansion of traditional shrimp cultivation, healthy management and improved culture technique are very much important to increase shrimp production in Bangladesh. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13001 J. bio-sci. 19 53-57, 2011